STATUS OF IGG ANTIBODIES AGAINST MYCOPLASMA GALLISEPTICUM IN NON-VACCINATED COMMERCIAL POULTRY BREEDER FLOCKS - A. Ahmad; M. Rabbani; T. Yaqoob; A. Ahmad; M. Z. Shabbir; F. Akhtar (Journal of Animal and Plant Sciences, 2008)
The age wise status of Mycoplasma gallisepticum (MG) infection of broiler breeding stock (MG nonvaccinated) in and around Lahore district was determined during the period of December, 2006 to November 2007. In this study, a total of 2777 serum samples were referred from different areas surrounding Lahore. History revealed that all the samples were from MG non vaccinated flocks and subjected to Indirect Enzyme Linked Immunosorbent assay (i-ELISA) to detect the status of IgG antibodies produced due to MG field exposure. The highest positive percentage(74.60%) of MG infection was found in breeding stock aging from 6 to 23 weeks while lowest (33.17%) in flocks of 60 to 76 th weeks of age. The result further revealed that the younger birds are more prone to MG infection compared to aged ones and presence of MG antibodies may not associate with clinical signs except in complicated cases.
Keywords: Mycoplasma gallisepticum; breeding stock; enzyme-linked immunosorbent assay (ELISA)